2019
DOI: 10.32614/rj-2019-024
|View full text |Cite
|
Sign up to set email alerts
|

shadow: R Package for Geometric Shadow Calculations in an Urban Environment

Abstract: This paper introduces the shadow package for R. The package provides functions for shadowrelated calculations in the urban environment, namely shadow height, shadow footprint and Sky View Factor (SVF) calculations, as well as a wrapper function to estimate solar radiation while taking shadow effects into account. All functions operate on a layer of polygons with a height attribute, also known as "extruded polygons" or 2.5D vector data. Such data are associated with accuracy limitations in representing urban en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
0
10
0
1
Order By: Relevance
“…Il est important de noter également que le volume des bâtiments est largement plus important à proximité du parc Montsouris. Afin d'étudier l'influence de l'ombre sur les températures relevées à Paris-Montsouris, nous avons réalisé une simulation de l'ombre autour de la station, en nous basant sur des données géographiques décrivant l'environnement et à partir de la librairie R shadow (Dorman et al, 2019). Nous avons utilisé R, logiciel de traitement de données, libre et largement répandu, utilisé dans plusieurs études récentes portant sur l'effet de l'ombre sur la température (Massetti et al, 2019 ;Erell et al, 2019 ;Moro et al, 2020).…”
Section: Données Et Méthodesunclassified
“…Il est important de noter également que le volume des bâtiments est largement plus important à proximité du parc Montsouris. Afin d'étudier l'influence de l'ombre sur les températures relevées à Paris-Montsouris, nous avons réalisé une simulation de l'ombre autour de la station, en nous basant sur des données géographiques décrivant l'environnement et à partir de la librairie R shadow (Dorman et al, 2019). Nous avons utilisé R, logiciel de traitement de données, libre et largement répandu, utilisé dans plusieurs études récentes portant sur l'effet de l'ombre sur la température (Massetti et al, 2019 ;Erell et al, 2019 ;Moro et al, 2020).…”
Section: Données Et Méthodesunclassified
“…Dealing with solar radiation and shadows is a common issue in Geographical Information Systems (GIS). This stems from a wide range of interests that go from visualization and rendering to many potential applications such as predicting the radiation at crucial environments like glaciers [ 2 ], the design of agroforestry exploitations [ 3 ] or, in the urban environment, project planning [ 4 ], the generation of solar radiation maps [ 5 ] essential for the deployment of concentrating solar power (CSP) plants [ 6 ], and for planning the optimal location and orientation of PV or solar thermal panels for distributed generation of electricity or heat for domestic applications on building roofs or facades [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. The latter application demands reliable models for solar radiation and shadow casting at the local level that can deal with the complexities of urban architecture, which has a tremendous impact on blocking the solar radiation of nearby areas.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the proper characterization of the shadows along the year is required for both the selection of the most convenient building surfaces and accurate performance modeling [7]. The use of geographic information systems (GIS) enriched with additional remote sensing information (e.g., LIDAR data) can be effectively used in the generation of solar cadasters and shadow studies in urban areas [8][9][10]. A thorough review of BIPV-related methods and tools can be found elsewhere [5,11,12].…”
Section: Introductionmentioning
confidence: 99%